Actual Problems of Emergency Abdominal Surgery - Victorovich Garbuzenko, Dmitry (IntechOpen, 2016)
The book "Actual Problems of Emergency Abdominal Surgery" was written by an international team of authors with extensive practical experience. It contains literature reviews describing some of the diseases and pathological conditions that occur in emergency surgical practice. The problems described are relevant for emergency abdominal surgery. We hope that the materials of the book will be of interest to anyone who considers it his or her specialty.